Porphyrin COF material and preparation method and application thereof
The porphyrin COF material prepared through step-by-step reaction solves the problem of the single function of the existing COF material, which leads to poor degradation of organic pollutants in water, and achieves the versatility and efficient degradation of the material.
Patent Information
- Application Number
- CN202510006189.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2045-01-03
AI Technical Summary
Due to the single function of existing covalent organic framework (COF) materials, it is difficult to effectively degrade organic pollutants in water, and the synthesis process is complex and difficult to produce on a large scale.
Using the preparation method of porphyrin COF material, by selecting tetracarboxyporphyrin and trivalent iron salt as raw materials, step-by-step reaction under reflux conditions, functional groups are introduced to ensure the structural integrity and versatility of the material.
The prepared porphyrin COF material has multiple functions of adsorption, photocatalysis and PDS activation, which significantly improves the degradation effect of organic pollutants in water and overcomes the limitations of the single function of traditional COF materials.
Smart Images

Figure CN119390970A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wastewater treatment material preparation, and specifically relates to a porphyrin COF material and a preparation method and application thereof. Background Art
[0002] With the booming development of the chemical, pharmaceutical and agricultural industries, the pollution of aquatic environments by organic synthetic compounds has become an increasingly serious problem, far exceeding the self-purification function of natural water bodies. These complex, toxic and difficult-to-decompose organic pollutants, including organic dyes, phenols and their derivatives, antibiotics, surfactants and pesticides, seriously threaten ecosystems and sustainable development. Therefore, the control and remediation of wastewater pollution, especially the treatment of organic pollutants in wastewater, has become a focus of global attention. This is not only crucial to improving the quality of aquatic ecosystems, but also can bring significant economic benefits.
[0003] At present, the main methods for treating organic pollutants in water include extraction, biodegradation, adsorption, ozone oxidation, ionizing radiation, Fenton oxidation, photocatalysis, and peroxydisulfate (PDS) activation. Although the above methods have effective treatment capabilities for organic pollutants at the laboratory level, they all have certain limitations in practical applications [Chemosphere, 2022, 286 131646]. For example, the extraction method is rapid and simple, but requires a large amount of organic solvents, which may cause secondary pollution. The biodegradation method is environmentally friendly and mild, but the treatment time is long, the footprint is large, the energy consumption is high, and the treatment capacity is limited. The adsorption method faces the problem of easy saturation of the adsorbent and difficulty in regenerating or replacing the adsorbent. The ozone oxidation method has strong oxidation ability and is easy to operate, but the investment and operating costs are high. The ionizing radiation method is effective, but the operation process is complicated. The Fenton oxidation method can oxidize most organic matter in water, but it is expensive and may have a greater negative impact on the environment. Although the photocatalytic method can completely convert organic pollutants into non-toxic inorganic substances under mild conditions, it faces problems such as low solar energy utilization, difficult catalyst separation, poor catalytic stability and low mineralization rate in its application [Science of the Total Environment, 2022, 812, 152434]. The PDS activation method has good degradation performance, but the PDS activation method still faces a series of challenges in its application. For example, ultraviolet, electrical, thermal and ultrasonic activation processes all require external energy input. For transition metal activation, if homogeneous metal ions are used, the activation effect is highly dependent on pH value, which may lead to the formation of precipitates and require additional treatment steps. In addition, some metal ions are toxic and may cause secondary environmental pollution after treatment. If heterogeneous metal catalysts, especially nanoparticle catalysts, are used, they may face metal leaching and agglomeration problems, thereby reducing the catalytic efficiency [Coordination Chemistry Reviews, 499 (2024), 215466].
[0004] Current covalent organic framework (COF) materials have attracted attention due to their high specific surface area and adjustable pore structure, but they have some disadvantages: many materials have a single function and lack multifunctionality; the synthesis process is complicated and difficult to mass produce; functionalization is difficult and the adaptability is insufficient, especially for the complete degradation of organic pollutants in water. These problems limit the effectiveness of existing COF materials in practical applications, and there is an urgent need to develop more advanced and multifunctional COF materials to meet the needs. Summary of the invention
[0005] The purpose of the present invention is to provide a porphyrin COF material and a preparation method and application thereof, so as to solve the technical problem that the existing COF materials have poor effect in degrading organic pollutants in water due to their single function.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing a porphyrin COF material, comprising the following steps: S1: react tetracarboxyl porphyrin, trivalent iron salt and solvent under reflux conditions, and after the reaction is completed, post-treat the reaction product to obtain Fe 3+ -TCPP solid; S2: Fe 3+ -TCPP solid, acyl chloride reagent and solvent react under reflux conditions. After the reaction is completed, the obtained reaction product is post-treated to obtain Fe 3+ -TCPP-COCl solid; S3: Put Fe 3+ -TCPP-COCl solid and p-phenylenediamine are ground to react. After the reaction is completed, the obtained reaction product is post-treated to obtain a porphyrin COF material.
[0007] Further, in S1, the ratio of the tetracarboxyl porphyrin, the trivalent iron salt and the solvent is 1 mol: (1.25-1.5) mol: 50 mL; the solvent is a mixture of CHCl3 and DMF in a volume ratio of (4-6): 1; The tetracarboxyl porphyrin is 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin; The trivalent iron salt is Fe2S3O 12 9H2O.
[0008] Furthermore, in S1, the parameters of the reflux conditions are: the reflux temperature is 130-140° C., and the reflux time is 3-5 h.
[0009] Furthermore, in S1, the post-treatment includes distillation, filtration and washing treatment performed in sequence; the distillation temperature is 70-72°C; the filtration is performed under normal pressure; and the washing treatment is performed by washing with methanol and deionized water 3-5 times each.
[0010] Further, in S2, the Fe 3+ -The molar ratio of TCPP solid to acyl chloride reagent is 1:(5~8); The solvent is CH2ClCH2Cl; the volume ratio of the acyl chloride reagent to the solvent is 1:(6-8); The acyl chloride reagent is one of SOCl2, PCl5 and PCl3; The parameters of the reflux conditions are: reflux temperature is 83-85° C., and reflux time is 2-4 h.
[0011] Furthermore, in S2, the post-treatment includes filtering and washing treatments performed sequentially; the filtration is performed under normal pressure; and the washing treatment is performed by washing with methanol and deionized water for 3 to 5 times respectively.
[0012] Further, in S3, the Fe 3+ The molar ratio of -TCPP-COCl solid to p-phenylenediamine is 1:(2-2.5); the grinding is performed at room temperature for 20-40 minutes.
[0013] Furthermore, in S3, the post-treatment includes washing and drying treatments performed in sequence; the washing is performed using ethanol and deionized water for 3 to 5 times each; the temperature of the drying treatment is 105 to 115°C and the time is 6 to 8 hours.
[0014] The invention also discloses a porphyrin COF material prepared by the preparation method.
[0015] The invention also discloses the application of the porphyrin COF material in degrading organic pollutants in water.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a preparation method of a porphyrin COF material. The method comprises the following steps: rationally selecting tetracarboxyl porphyrin and trivalent iron salt as raw materials, reacting under reflux conditions, and optimizing reaction parameters and post-processing steps, thereby improving the purity and yield of the prepared porphyrin COF material. The preparation method disclosed by the invention adopts a step-by-step reaction path method to gradually introduce functional groups to ensure the structural integrity and multifunctionality of the porphyrin COF material, especially introducing Fe³⁺ ions through trivalent iron salt, and significantly enhancing the photocatalytic and PDS activation performance of the porphyrin COF material in combination with other raw materials, so as to prepare a multifunctional porphyrin COF material having adsorption, photocatalysis and PDS activation. Compared with the prior art, the invention overcomes the limitations of the traditional preparation method and solves the technical problem that the existing COF material has a poor effect in degrading organic pollutants in water due to its single function.
[0017] Furthermore, the dosage ratio of tetracarboxyl porphyrin, trivalent iron salt and solvent is 1 mol: (1.25-1.5) mol: 50 mL, which helps to optimize the reaction conditions and ensure the high efficiency of the reaction and the purity of the product; the use of a mixture of CHCl3 and DMF as a solvent not only improves the solubility of the reactants, but also helps to improve the quality of the product; the use of 5, 10, 15, 20-tetrakis (4-carboxyphenyl) porphyrin as a raw material has good optical properties and catalytic activity, which improves the performance of the final porphyrin COF material; the use of Fe2S3O 12 9H2O as a raw material is cheap and readily available.
[0018] Furthermore, Fe 3+ -TCPP solid, the reflux temperature is 130~140℃, and the reflux time is 3~5h, which reduces the possibility of side reactions and ensures that the reactants are fully converted into the target products, thereby improving the selectivity and yield of the products.
[0019] Furthermore, Fe 3+ -TCPP solid, distillation, filtration and washing treatment are carried out in sequence to ensure the purity of the reaction product and remove unreacted raw materials and impurities; clear provisions on distillation temperature and washing treatment times are helpful to obtain high-purity Fe 3+ -TCPP solid, further improving the efficiency and effect of subsequent reactions.
[0020] Furthermore, Fe 3+ -TCPP-COCl solid fixes Fe 3+ -The molar ratio of TCPP solid to acyl chloride reagent and the reflux conditions ensure the high efficiency and selectivity of the reaction and reduce the formation of by-products; at the same time, the diverse selection of acyl chloride reagents provides flexibility, allowing the reaction to be optimized under different conditions.
[0021] Furthermore, Fe 3+ -TCPP-COCl solid, filtering and washing treatments are carried out in sequence, making the entire process more efficient and able to effectively remove impurities; filtering at normal pressure, combined with washing with methanol and deionized water, improves the purity of the product and reduces the residual potential pollutants.
[0022] Furthermore, Fe 3+ The molar ratio of -TCPP-COCl solid to p-phenylenediamine is 1:(2~2.5), which helps to optimize the reaction efficiency and ensure the quality of the final product; controlling the grinding time to 20~40min can effectively promote the reaction and avoid material loss or product denaturation caused by excessive grinding; in the step of preparing the porphyrin COF material, washing and drying treatments are carried out in sequence, which helps to remove unreacted raw materials and by-products, thereby improving the quality of the final product; washing with ethanol and deionized water 3~5 times each can effectively remove surface adsorbed impurities and solvent residues, ensure the purity of the material and improve its catalytic performance; setting the drying temperature to 105~115℃ and the drying time to 6~8h ensures that while removing moisture from the material, the material will not cause structural damage or changes in physical properties due to high temperature.
[0023] The present invention also discloses a porphyrin COF material prepared by the above method, whose stable metal porphyrin structure ensures the chemical stability of the porphyrin COF material during multiple uses, reduces the replacement frequency and improves the economic benefit; in addition, the present invention adopts a step-by-step reaction synthesis strategy, and the material formula used in the reaction is adjustable, which is convenient for customization of specific applications; the prepared porphyrin COF material has multiple functions of adsorption, photocatalysis and PDS activation, is suitable for the fields of environmental governance and renewable energy, and shows good application potential in the fields of water treatment and photocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a SEM (scanning electron microscope) image of the porphyrin COF material prepared in Example 3 of the present invention; Figure 2 This is an elemental scan image of the porphyrin COF material prepared in Example 3 of the present invention; Among them: a) - SEM general image; b) - C element distribution map; c) - N element distribution map; d) - O element distribution map; e) - Fe element distribution map; Figure 3 This is the infrared spectrum of the porphyrin COF material prepared in Example 3 of the present invention; Figure 4 The PXRD (powder X-ray diffraction) spectrum of the porphyrin COF material prepared in Example 3 of the present invention; Figure 5 This is the XPS (X-ray photoelectron spectroscopy) spectrum of the porphyrin COF material prepared in Example 3 of the present invention; Among them: (a) - XPS general spectrum; (b) - XPS fine spectrum of C; (c) - XPS fine spectrum of N; (d) - XPS fine spectrum of O; (e) - XPS fine spectrum of Fe; Figure 6 This is a thermal stability diagram of the porphyrin COF material prepared in Example 3 of the present invention; Figure 7 This is a graph showing the nitrogen adsorption-desorption experimental data of the porphyrin COF material prepared in Example 3 of the present invention; Figure 8 The UV-visible diffuse reflectance spectrum of the porphyrin COF material prepared in Example 3 of the present invention; Among them: (a), UV-visible diffuse reflectance spectrum; (b), acquisition diagram of material band gap. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0027] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0028] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0030] The present invention provides a method for preparing a porphyrin COF material, comprising the following steps: S1: tetracarboxyl porphyrin, trivalent iron salt and solvent are reacted under reflux conditions. After the reaction is completed and the temperature is lowered to room temperature, the obtained reaction product is sequentially distilled, filtered and washed to obtain Fe 3+ -TCPP solid; S2: Fe 3+ -TCPP solid, acyl chloride reagent and solvent react under reflux conditions. After the reaction is completed and the temperature drops to room temperature, the obtained reaction product is filtered and washed in turn to obtain Fe 3+ -TCPP-COCl solid; S3: Put Fe 3+ -TCPP-COCl solid and p-phenylenediamine (PD) were ground and reacted at room temperature. After the reaction, the obtained reaction product was washed and dried in turn to obtain porphyrin COF material (Fe 3+-Por-COF).
[0031] Preferably, in S1, the dosage ratio of the tetracarboxylic porphyrin, the trivalent iron salt and the solvent is 1 mol: (1.25-1.5) mol: 50 mL; the solvent is a mixture of CHCl3 (chloroform) and DMF (dimethylformamide) in a volume ratio of (4-6): 1; the parameters of the reflux conditions are: the reflux temperature is 130-140°C, and the reflux time is 3-5h; the distillation temperature is 70-72°C; the filtration is carried out under normal pressure; and the washing treatment is carried out by washing 3-5 times each with methanol and deionized water.
[0032] Preferably, in S1, the tetracarboxyl porphyrin is 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin; the trivalent iron salt is Fe2S3O 12 9H2O.
[0033] Preferably, in S2, Fe 3+ -TCPP solid and acyl chloride reagent molar ratio is 1: (5~8); acyl chloride reagent and solvent volume ratio is 1: (6~8); reflux condition parameters are: reflux temperature is 83~85℃, reflux time is 2~4h; solvent is CH2ClCH2Cl (1,2-dichloroethane); acyl chloride reagent is one of SOCl2, PCl5 and PCl3; filtration is carried out under normal pressure; washing treatment is washing 3~5 times with methanol and deionized water respectively.
[0034] Preferably, in S3, Fe 3+ The molar ratio of -TCPP-COCl solid to p-phenylenediamine is 1:(2~2.5); grinding is performed at room temperature for 20~40 minutes; washing is performed using ethanol and deionized water for 3~5 times respectively; the drying temperature is 105~115°C and the drying time is 6~8 hours.
[0035] In S1, when the tetracarboxyl porphyrin is 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) and the trivalent iron salt is ferric sulfate (Fe2(SO4)3∙9H2O), Fe 3+ -TCPP solid reaction process is shown below: ; Since Fe2(SO4)3∙9H2O will produce trivalent iron ions after dissolution, and the four nitrogen atoms in the porphyrin center of TCPP have good coordination ability, under reflux conditions, the trivalent iron ions will gradually react with the four nitrogen atoms in the porphyrin center to form trivalent iron porphyrin (Fe 3+-TCPP solid); Due to the strong coordination relationship of the coordination reaction, the trivalent iron ions will not fall off and agglomerate at will during the use of the porphyrin COF material, which reduces the possibility of secondary pollution.
[0036] In S2, when the acyl chloride reagent is dichlorophenol (SOCl2), Fe 3+ The reaction process of -TCPP-COCl solid is shown in the following formula: ; Fe 3+ -TCPP solid and SOCl2 undergo chlorination reaction to make Fe 3+ The carboxyl groups in the TCPP solid are converted into acyl chloride groups to form acyl chloride trivalent iron porphyrin (Fe 3+ -TCPP-COCl solid).
[0037] In S3, Fe 3+ The reaction process of -Por-COF (porphyrin COF material) is shown below: ; Fe 3+ The acyl chloride group in the TCPP-COCl solid will undergo a condensation reaction with the amino group in PD to generate Fe 3+ -Por-COF and HCl.
[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0039] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0040] Example 1 A method for preparing a porphyrin COF material comprises the following steps: Step 1: 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin, Fe2S3O 12·9H2O and the solvent react under reflux conditions. After the reaction is completed and the temperature drops to room temperature, the obtained reaction product is sequentially distilled, filtered and washed to obtain Fe 3+ -TCPP solid; wherein 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin and Fe2S3O 12 The molar ratio of 9H2O is 1 mol:1.25 mol; the amount of solvent used is 50 mL, and the solvent is a mixture of CHCl3 and DMF with a volume ratio of 4:1; the distillation temperature is 70°C; the filtration is carried out under normal pressure; the washing treatment is carried out by washing with methanol and deionized water for 3 times each; the parameters of the reflux conditions are: the reflux temperature is 130°C, and the reflux time is 3 hours; Step 2: Add Fe 3+ -TCPP solid, SOCl2 and solvent react under reflux conditions. After the reaction is completed and the temperature drops to room temperature, the obtained reaction product is filtered and washed in turn to obtain Fe 3+ -TCPP-COCl solid; among which, Fe 3+ -The molar ratio of TCPP solid to SOCl2 is 1:5; the solvent is CH2ClCH2Cl; the volume ratio of SOCl2 to CH2ClCH2Cl is 1:6; the parameters of the reflux conditions are: reflux temperature is 83°C, reflux time is 2h; filtration is carried out under normal pressure; washing treatment is carried out by washing with methanol and deionized water 3 times each; Step 3: Fe 3+ -TCPP-COCl solid and p-phenylenediamine (PD) were ground and reacted at room temperature. After the reaction, the obtained reaction product was washed and dried in turn to obtain porphyrin COF material (Fe 3+ -Por-COF); among which, Fe 3+ The molar ratio of -TCPP-COCl solid to p-phenylenediamine is 1:2; the grinding is performed at room temperature for 20 minutes; the washing is performed 3 times each with ethanol and deionized water; the drying temperature is 105°C and the drying time is 6 hours.
[0041] Example 2 A method for preparing a porphyrin COF material comprises the following steps: Step 1: 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin, Fe2S3O 12 ·9H2O and the solvent react under reflux conditions. After the reaction is completed and the temperature drops to room temperature, the obtained reaction product is sequentially distilled, filtered and washed to obtain Fe 3+ -TCPP solid; wherein 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin and Fe2S3O 12The molar ratio of 9H2O is 1 mol:1.4 mol; the amount of solvent used is 50 mL, and the solvent is a mixture of CHCl3 and DMF with a volume ratio of 5:1; the distillation temperature is 70°C; the filtration is carried out under normal pressure; the washing treatment is carried out by washing with methanol and deionized water 4 times each; the parameters of the reflux conditions are: the reflux temperature is 135°C, and the reflux time is 4 hours; Step 2: Add Fe 3+ -TCPP solid, SOCl2 and solvent react under reflux conditions. After the reaction is completed and the temperature drops to room temperature, the obtained reaction product is filtered and washed in turn to obtain Fe 3+ -TCPP-COCl solid; among which, Fe 3+ -The molar ratio of TCPP solid to SOCl2 is 1:6; the solvent is CH2ClCH2Cl; the volume ratio of SOCl2 to CH2ClCH2Cl is 1:7; the parameters of the reflux conditions are: reflux temperature is 84°C, reflux time is 3h; filtration is carried out under normal pressure; washing treatment is carried out by washing with methanol and deionized water 4 times each; Step 3: Fe 3+ -TCPP-COCl solid and p-phenylenediamine (PD) were ground and reacted at room temperature. After the reaction, the obtained reaction product was washed and dried in turn to obtain porphyrin COF material (Fe 3+ -Por-COF); among which, Fe 3+ The molar ratio of -TCPP-COCl solid to p-phenylenediamine is 1:2.3; the grinding is performed at room temperature for 30 minutes; the washing is performed 4 times each with ethanol and deionized water; the drying temperature is 110°C and the drying time is 7 hours.
[0042] Example 3 A method for preparing a porphyrin COF material comprises the following steps: Step 1: 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin, Fe2S3O 12 ·9H2O and the solvent react under reflux conditions. After the reaction is completed and the temperature drops to room temperature, the obtained reaction product is sequentially distilled, filtered and washed to obtain Fe 3+ -TCPP solid; wherein 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin and Fe2S3O 12 The molar ratio of 9H2O is 1 mol:1.5 mol; the amount of solvent used is 50 mL, and the solvent is a mixture of CHCl3 and DMF with a volume ratio of 6:1; the distillation temperature is 70°C; the filtration is carried out under normal pressure; the washing treatment is carried out by washing with methanol and deionized water 5 times each; the parameters of the reflux conditions are: the reflux temperature is 140°C, and the reflux time is 5 hours; Step 2: Add Fe 3+ -TCPP solid, SOCl2 and solvent react under reflux conditions. After the reaction is completed and the temperature drops to room temperature, the obtained reaction product is filtered and washed in turn to obtain Fe 3+ -TCPP-COCl solid; among which, Fe 3+ -The molar ratio of TCPP solid and SOCl2 is 1:8; the solvent is CH2ClCH2Cl; the volume ratio of SOCl2 and CH2ClCH2Cl is 1:8; the parameters of the reflux conditions are: reflux temperature is 85°C, reflux time is 4h; filtration is carried out under normal pressure; washing treatment is carried out by washing with methanol and deionized water 5 times each; Step 3: Fe 3+ -TCPP-COCl solid and p-phenylenediamine (PD) were ground and reacted at room temperature. After the reaction, the obtained reaction product was washed and dried in turn to obtain porphyrin COF material (Fe 3+ -Por-COF); among which, Fe 3+ The molar ratio of -TCPP-COCl solid to p-phenylenediamine is 1:2.5; the grinding is performed at room temperature for 40 minutes; the washing is performed 5 times each with ethanol and deionized water; the drying temperature is 115°C and the drying time is 8 hours.
[0043] Example 4 A method for preparing a porphyrin COF material comprises the following steps: Step 1: 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin, Fe2S3O 12 ·9H2O and the solvent react under reflux conditions. After the reaction is completed and the temperature drops to room temperature, the obtained reaction product is sequentially distilled, filtered and washed to obtain Fe 3+ -TCPP solid; wherein the molar ratio of 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin and FeCl3·6H2O is 1 mol:1.5 mol; the amount of solvent used is 50 mL, and the solvent is a mixture of CHCl3 and DMF in a volume ratio of 6:1; the distillation temperature is 70°C; the filtration is carried out under normal pressure; the washing treatment is carried out by washing with methanol and deionized water for 5 times each; the parameters of the reflux conditions are: the reflux temperature is 140°C, and the reflux time is 5h.
[0044] Step 2: Add Fe 3+ -TCPP solid, SOCl2 and solvent react under reflux conditions. After the reaction is completed and the temperature drops to room temperature, the obtained reaction product is filtered and washed in turn to obtain Fe 3+ -TCPP-COCl solid; among which, Fe 3+-The molar ratio of TCPP solid and SOCl2 is 1:8; the solvent is CH2ClCH2Cl; the volume ratio of SOCl2 and CH2ClCH2Cl is 1:8; the parameters of the reflux conditions are: reflux temperature is 85°C, reflux time is 4h; filtration is carried out under normal pressure; washing treatment is carried out by washing with methanol and deionized water 5 times each; Step 3: Fe 3+ -TCPP-COCl solid and p-phenylenediamine (PD) were ground and reacted at room temperature. After the reaction, the obtained reaction product was washed and dried in turn to obtain porphyrin COF material (Fe 3+ -Por-COF); among which, Fe 3+ The molar ratio of -TCPP-COCl solid to p-phenylenediamine is 1:2.5; the grinding is performed at room temperature for 40 minutes; the washing is performed 5 times each with ethanol and deionized water; the drying temperature is 115°C and the drying time is 8 hours.
[0045] Example 5 A method for preparing a porphyrin COF material comprises the following steps: Step 1: 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin, Fe2S3O 12 ·9H2O and the solvent react under reflux conditions. After the reaction is completed and the temperature drops to room temperature, the obtained reaction product is sequentially distilled, filtered and washed to obtain Fe 3+ -TCPP solid; wherein 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin and Fe2S3O 12 The molar ratio of 9H2O is 1 mol:1.5 mol; the amount of solvent used is 50 mL, and the solvent is a mixture of CHCl3 and DMF in a volume ratio of 6:1; the distillation temperature is 70°C; the filtration is carried out under normal pressure; the washing treatment is carried out using methanol and deionized water for 5 times each; the parameters of the reflux conditions are: the reflux temperature is 140°C, and the reflux time is 5 hours.
[0046] Step 2: Add Fe 3+ -TCPP solid, PCl5 and solvent react under reflux conditions. After the reaction is completed and the temperature drops to room temperature, the obtained reaction product is filtered and washed in turn to obtain Fe 3+ -TCPP-COCl solid; among which, Fe 3+ -The molar ratio of TCPP solid to PCl5 is 1:8; the solvent is CH2ClCH2Cl; the volume ratio of PCl5 to CH2ClCH2Cl is 1:8; the parameters of the reflux conditions are: reflux temperature is 85°C, reflux time is 4h; filtration is carried out under normal pressure; washing treatment is carried out by washing with methanol and deionized water 5 times each; Step 3: Fe 3+ -TCPP-COCl solid and p-phenylenediamine (PD) were ground and reacted at room temperature. After the reaction, the obtained reaction product was washed and dried in turn to obtain porphyrin COF material (Fe 3+ -Por-COF); among which, Fe 3+ The molar ratio of -TCPP-COCl solid to p-phenylenediamine is 1:2.5; the grinding is performed at room temperature for 40 minutes; the washing is performed 5 times each with ethanol and deionized water; the drying temperature is 115°C and the drying time is 8 hours.
[0047] Example 6 A method for preparing a porphyrin COF material comprises the following steps: Step 1: 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin, Fe2S3O 12 ·9H2O and the solvent react under reflux conditions. After the reaction is completed and the temperature drops to room temperature, the obtained reaction product is sequentially distilled, filtered and washed to obtain Fe 3+ -TCPP solid; wherein 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin and Fe2S3O 12 The molar ratio of 9H2O is 1 mol:1.5 mol; the amount of solvent used is 50 mL, and the solvent is a mixture of CHCl3 and DMF in a volume ratio of 6:1; the distillation temperature is 70°C; the filtration is carried out under normal pressure; the washing treatment is carried out using methanol and deionized water for 5 times each; the parameters of the reflux conditions are: the reflux temperature is 140°C, and the reflux time is 5 hours.
[0048] Step 2: Add Fe 3+ -TCPP solid, PCl3 and solvent react under reflux conditions. After the reaction is completed and the temperature drops to room temperature, the obtained reaction product is filtered and washed in turn to obtain Fe 3+ -TCPP-COCl solid; among which, Fe 3+ -The molar ratio of TCPP solid to PCl3 is 1:8; the solvent is CH2ClCH2Cl; the volume ratio of PCl3 to CH2ClCH2Cl is 1:8; the parameters of the reflux conditions are: reflux temperature is 85°C, reflux time is 4h; filtration is carried out under normal pressure; washing treatment is carried out by washing with methanol and deionized water 5 times each; Step 3: Fe 3+ -TCPP-COCl solid and p-phenylenediamine (PD) were ground and reacted at room temperature. After the reaction, the obtained reaction product was washed and dried in turn to obtain porphyrin COF material (Fe 3+-Por-COF); among which, Fe 3+ The molar ratio of -TCPP-COCl solid to p-phenylenediamine is 1:2.5; the grinding is performed at room temperature for 40 minutes; the washing is performed 5 times each with ethanol and deionized water; the drying temperature is 115°C and the drying time is 8 hours.
[0049] The porphyrin COF materials prepared in different embodiments of the present invention were tested for pollutant degradation performance according to the national standard in the field of photocatalysis. The specific national standard is as follows: GB / T23762-2009 (test method for purification of aqueous solution system of photocatalytic material). The test results are shown in Table 1. It can be seen from Table 1 that the porphyrin COF materials prepared in the present invention have a good degradation effect on both organic dyes and antibiotics; in particular, the porphyrin COF materials have a better effect when adsorption, photocatalysis and PDS activation act synergistically. For rhodamine, the synergistic effect of the three can be completely degraded in 30 minutes, while at least 90 minutes are required when they act alone; for tetracycline, the synergistic effect of the three has little effect on the degradation time, but greatly improves the degradation efficiency; and the degradation effect of the porphyrin COF material does not change much after 5 cycles, indicating that it has high stability.
[0050] Table 1 Pollutant degradation performance data of porphyrin COF materials prepared in different embodiments
[0051] Note: The experiments were carried out at room temperature of 20°C, pH value of 7, and xenon lamp power of 500W.
[0052] Figure 1 This is a SEM image of the porphyrin COF material prepared in Example 3 of the present invention. It can be seen from the image that the porphyrin COF material prepared in the present invention has a layered structure.
[0053] Figure 2 This is an element point scanning image of the porphyrin COF material prepared in Example 3 of the present invention. It can be seen that C, O, N and Fe elements are evenly distributed in the porphyrin COF material, which also proves the successful coordination of trivalent iron ions.
[0054] Figure 3 This is the infrared spectrum of the porphyrin COF material prepared in Example 3 of the present invention. From the 1514 cm -1 and 1643~1641cm -1 The infrared absorption peak at , corresponding to the stretching vibration band of amide bond NH and C=O, can indicate that the amide bond-connected porphyrin COF material has been successfully formed.
[0055] Figure 4The PXRD spectrum of the porphyrin COF material prepared in Example 3 of the present invention shows two main diffraction peaks at 2.1° and 7.8°, and a diffuse mantou peak appears at 22.4°, which belongs to the π-π stacking diffraction peak of the porphyrin COF material obtained in the layered material, indicating that Fe 3+ -Por-COF has a certain degree of crystallinity.
[0056] Figure 5 This is the XPS spectrum of the porphyrin COF material prepared in Example 3 of the present invention. It can be seen that the C 1s fine spectrum is located at 284.8, 285.30 and 288.20 eV, the N 1s fine spectrum is located at 398.24, 399.91 and 402.46 eV, the O 1s fine spectrum is located at 531.04 and 532.83 eV, and the Fe 2p fine spectrum is located at 711.29 eV. There is also a satellite peak around it, which once again proves the successful synthesis of trivalent iron porphyrin.
[0057] Figure 6 The thermal stability diagram of the porphyrin COF material prepared in Example 3 of the present invention shows that in the first stage, at 30-90°C, the reduction in the initial weight of the porphyrin COF material corresponds to the evaporation of adsorbed water and residual solvent molecules; in the second stage, from 90-530°C, the gradual weight loss of the porphyrin COF material is due to the decomposition of the functional groups on the upper edge; in the third stage, at 530-800°C, the drastic weight loss of the porphyrin COF material marks the beginning of the structural collapse and decomposition of the porphyrin COF material; at 800°C, the porphyrin COF material also exhibits a mass retention rate of 59.45%, indicating that Fe 3+ -Por-COF has good thermal stability.
[0058] Figure 7 The nitrogen adsorption-desorption experimental data of the porphyrin COF material prepared in Example 3 of the present invention is shown in FIG. The results show that the porphyrin COF material has a type III adsorption mode, which is a characteristic of a material with a mesoporous structure. From the data processing, it can be seen that the surface area of the porphyrin COF material is 48.76 m 2 / g, and the total pore volume is 0.231cm 3 / g, the average pore size is 25.82nm, so Fe 3+ -Por-COF has potential adsorption properties.
[0059] Figure 8 This is the UV-visible diffuse reflectance spectrum of the porphyrin COF material prepared in Example 3 of the present invention. It can be seen that due to the highly conjugated structure of the porphyrin in the porphyrin COF material, Fe 3+ -Por-COF exhibits full spectral response (300-700nm), covering almost the entire visible light region; Fe 3+The band gap of -Por-COF was calculated by the Kubelka–Munk equation and was found to be 2.5 eV.
[0060] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a porphyrin COF material, characterized in that: The following steps are involved: S1: react tetracarboxyl porphyrin, trivalent iron salt and solvent under reflux conditions, and after the reaction is completed, post-treat the reaction product to obtain Fe 3+ -TCPP solid; S2: Fe 3+ -TCPP solid, acyl chloride reagent and solvent react under reflux conditions. After the reaction is completed, the obtained reaction product is post-treated to obtain Fe 3+ -TCPP-COCl solid; S3: Put Fe 3+ -TCPP-COCl solid and p-phenylenediamine are ground to react. After the reaction is completed, the obtained reaction product is post-treated to obtain a porphyrin COF material.
2. The method for preparing a porphyrin COF material according to claim 1, characterized in that: In S1, the ratio of the tetracarboxyl porphyrin, the trivalent iron salt and the solvent is 1 mol: (1.25-1.5) mol: 50 mL; the solvent is a mixture of CHCl3 and DMF in a volume ratio of (4-6): 1; The tetracarboxyl porphyrin is 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin; The trivalent iron salt is Fe2S3O 12 ·9H2O.
3. The method for preparing a porphyrin COF material according to claim 1, characterized in that: In S1, the parameters of the reflux conditions are: reflux temperature is 130-140° C., and reflux time is 3-5 h.
4. The method for preparing a porphyrin COF material according to claim 1, characterized in that: In S1, the post-treatment includes distillation, filtration and washing treatment performed in sequence; the distillation temperature is 70-72°C; the filtration is performed under normal pressure; the washing treatment is performed by washing with methanol and deionized water 3-5 times each.
5. The method for preparing a porphyrin COF material according to claim 1, characterized in that: In S2, the Fe 3+ -The molar ratio of TCPP solid to acyl chloride reagent is 1:(5~8); The solvent is CH2ClCH2Cl; the volume ratio of the acyl chloride reagent to the solvent is 1:(6-8); The acyl chloride reagent is one of SOCl2, PCl5 and PCl3; The parameters of the reflux conditions are: reflux temperature is 83-85° C., and reflux time is 2-4 h.
6. The method for preparing a porphyrin COF material according to claim 1, characterized in that: In S2, the post-treatment includes filtering and washing treatments performed in sequence; the filtration is performed under normal pressure; the washing treatment is performed by washing with methanol and deionized water for 3 to 5 times respectively.
7. The method for preparing a porphyrin COF material according to claim 1, characterized in that: In S3, the Fe 3+ The molar ratio of -TCPP-COCl solid to p-phenylenediamine is 1:(2-2.5); the grinding is performed at room temperature for 20-40 minutes.
8. The method for preparing a porphyrin COF material according to claim 1, characterized in that: In S3, the post-treatment includes washing and drying treatments performed in sequence; the washing is performed using ethanol and deionized water for 3 to 5 times each; the temperature of the drying treatment is 105 to 115° C., and the time is 6 to 8 hours.
9. A porphyrin COF material, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Use of the porphyrin COF material according to claim 9 in degrading organic pollutants in water.
Citation Information
Patent Citations
Preparation method of Meso-tetrakis(4-chloroformylphenyl)porphyrin
CN106397448A
Biochar-ferriporphyrin composite material, method for preparing same and application of biochar-ferriporphyrin composite material
CN109126873A
Preparation method of porphyrin COF and carbon nitride composite material and application in photocatalytic degradation of organic dyes
CN110227550A
Application of metalloporphyrin-mesoporous organic silicon oxide composite material in photocatalytic degradation of organic pollutants
CN111841636A
Preparation and application of porphyrin-modified Fe-based MOF photocatalytic material
CN114713285A